Bhadrakali - 102 - Brig Ajai Singh (2022)
Image courtesy: Brig A.P. Singh - www.collectingmoment.in Kali, a fierce form of Parvathi, is seen here with a trident, skull on a stick and is dancing on a corpse. Kali was born out of Parvathi when the demon Rakthabeejasura needed to be slayed.